Frasemer som konstituenter i løbende tekst - Jakobsen, Lisbeth Falster (HERMES - Journal of Language and Communication in Business, 2005)
Phrasemes are prefabricated items on the expression side as well as the content side. On the content side their imbedding in a text depends on the syntactic slots which the phraseme provides, from valency slots somewhere in the sentence construction to an independent function as a texteme. On the content side the dependency consists in the semantic consistency with the text world. The most interesting phrasemes are those which have a double content layer. Here the literal content does not ﬁt into the isotopies of the text world, and the embedding is made via the idiomatic content layer which the recipient of the text is presupposed to be familiar with. If the phraseme has a semantic transparency, it may be the paradigmatic point of departure for variations of the various constituents of the phraseme. It may also be enlarged by constituents which match the isotopies of the primary text, whereby it reinforces the coherence of the content. Various functions of phrasemes and phraseme variation in running text are demonstrated.